Core Patterns of Lexical Use in a Comparable Corpus of English Narrative Prose - Laviosa, Sara (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis paper investigates the linguistic nature of English translated texts. The author' corpus consists of a sub-section of the English Comparable Corpus (ECC). It comprises two collections of narrative prose in English: one is made up of translations from a variety of source languages, the other includes original English texts produced during a similar time span. The study reveals four patterns of lexical use in translated versus original texts.